Unusual presentation of parotid gland adenoid cystic carcinoma : A case presentation and literature review - N. Ouatassi, Assistant professor of ENT (Elsevier, 2022)
Adenoid cystic carcinoma (ACC) represents approximately 10% of all epithelial salivary neoplasms and most commonly involves the parotid gland.We report CT and MRI finding of a 38-year-old young man presented to our ENT department with 02 years history of an external auditory canal stenosis. Physical examination revealed bilateral parotid gland swelling with a complete stenosis of the left external auditory canal.Temporal bone contrast enhanced CT-SCAN revealed is an isodense enhancing mass measuring 4 cm involving posterior and inferior external auditory canal wall, and invading the superficial lobe of the homolateral parotid gland. No bone erosion was noted. MRI investigation has shown a tumor process highly suspicious of malignancy centered on the left EAC involving the superficial lobe of the homolateral parotid gland. Adenoid cystic carcinoma (ACC) of the parotid gland was the final diagnosis, after surgical biopsy and histopathological examination. The Pre-operative check-up demonstrated multiple round shape lung lesions suggestive of multiple metastases. Considering the metastatic stage of the tumor, a collegial decision to adopt a palliative treatment approach based on chemotherapy was taken by the multidisciplinary oncology board.